THE EFFECT OF CAPITAL GAIN AND DIVISION OF DIVIDENDS ON SHARE TRADING VOLUME IN PT. UNILEVER INDONESIA Tbk - Aladini, Anggi; Nurulrahmatia, Nafisah (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This study aims to determine, understand, and analyze the effect of capital gains and dividends on the volume of stock trading at PT. Unilever Indonesia tbk. the population in this study is the balance sheet financial statement data for 38 years and the sample of this study is 8 years with the sampling used is an associative approach. The statistical tools used are classical assumption test, multiple linier regression, correlation coefficient, determination coefficient, 2 party t based on data analysis from 2012 to 2018, it shows that capital gains and dividend distribution have a significant effect on stock trading volume. While the simultaneous capital gain and dividend distribution have no effect on stock trading volume.